Combined heat treatment of metal materials. Issue 4 (4th July 2016) - Kotlan, Václav; Hamar, Roman; Pánek, David; Doležel, Ivo
Abstract : Purpose: – The purpose of this paper is to propose and analyze a combined heat treatment of metal materials, consisting in classic induction pre-heating and/or post-heating and full heating by laser beam. This technology is prospective for some kinds of surface hardening and welding because its application leads to lowering of temperature gradients at the heated spots, which substantially reduces local residual mechanical strains and stresses. Design/methodology/approach: – The task was solved like the 3D hard-coupled problem for electromagnetic field, temperature field and field of displacements. It was solved numerically using the techniques based on the FEM. For solution was used commercial software COMSOL Multiphysics, some parts were solved using own scripts in the software Agros. Findings: – In the paper are shown results of the numerical solution and experimental measured data. Due the work the authors found that the influence of the pre-heating and post-heating really leads to limit the temperature gradients and from other measurements is clear that also to improving of the welding. Originality/value: – The paper presents fully 3D nonlinear and nonstationary mathematical model of hybrid laser welding, its numerical solution experimental verification.